IF CosX+SinX=?2.CosX P.T CosX-SinX=?2.SinX

Asked by chethan U | 22nd Jul, 2012, 05:33: PM

Expert Answer:

Answer : Given : cosA+ sinA = (underroot2 )*cosA 
To prove : cosA - sinA = (underroot2 )*sinA
 
we have ,
=> (cosA+sinA)2 + (cosA -sinA) = 2
=> ( (underroot 2 ) *(cosA) ) + (cosA-sinA)= 2  { using given equation}
=> 2cos2A + (cosA-sinA)2 = 2  
=> (cosA-sinA)= 2 - 2cos2A
=> (cosA - sinA)2 = 2 ( sin2A )    { using 1 - cos2A = sin2A }
 
taking the square root both the sides we get ,
 
=>  cosA- sinA = (underroot2 )*sinA
            Hence Proved 

Answered by  | 22nd Jul, 2012, 07:41: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.